Reinhold Messner:Antarktis als Reisebericht - Lukic, Anita (2012)
Anders als bei früheren Expeditionen, die von der magnetischen Anziehungskraft dieses unerforschten Kontinents solche körperlichen und vor allem auch seelischen Strapazen auf sich nahmen und den „Eroberungsgeist“ in die Welt tragen wollten, sind heutige Abenteurer weniger auf Forschung, sondern mehr auf die „Extremerfahrung“ Antarktis orientiert. Ein heutiger Abenteurer ist auf der Suche nach dem ultimativen „Kick“ – je extremer, desto besser. Er will seine Grenzen herausfinden und mutet sich alle möglichen Strapazen zu, um sich selbst zu verwirklichen und zu wissen, wie viel er sich zumuten kann. Die Antarktis ist daher der perfekte Ort, um diese Extremerfahrung zu machen und dies ist auch in der Art und Weise zu sehen, wie er seine Erfahrungen an die Öffentlichkeit kommuniziert. Ein moderner Abenteurer würde bezüglich seiner Reisebibliothek (sofern er eine mitnimmt) wohl eine „digitalisierte“ Bibliothek nutzen: er kann seine Bücher während der Planung alle auf sein Kindle oder sein Tablet-PC herunterladen und hat so, mit wenig Aufwand, alle Werke der Antarktisforscher zur Hand. Wenn ein heutiger Forscher auf Reisen geht, dann tut er das im Grunde nicht mehr alleine. Er vernetzt sich während seiner Expedition über alle modernen Social-Media-Kanäle (Facebook, Twitter, Blog usw.) und lässt so die breite Öffentlichkeit an seinen Erfahrungen direkt teilhaben. Er wird also auf seiner Expedition medial „begleitet“. Im Gegensatz zu den früheren Antarktisforschern, oder sogar Reinhold Messner selbst, wäre ein heutiger Antarktisforscher ein „vernetzter“. In diesem Sinne vergehen nicht viele Monate, bis der Forscher seine Eindrücke, Erfahrungen und Forschungsergebnisse veröffentlicht, er kann es jetzt sofort machen – direkt, zeitnah und (in gewisser Weise) auch ungefiltert. Hier liegt allerdings auch das Problem, dass gewisse Details oder Geschehnisse womöglich nicht redigiert werden können, da diese Geschehnisse direkt kommuniziert werden. Dinge, die sich für ein gedrucktes Buch leichter „herausklammern“ lassen könnten. In diesem Sinne kann Messners Reisebericht als wohl eines der letzten „klassischen“ Antarktisreiseberichte gesehen werden: die Planung, der Ablauf und auch das Schreiben selbst erfolgte nach „alten“ Maßstäben. Messner selbst hat seinen Reisebericht erst Monate nach seiner Expedition veröffentlicht. Dies ermöglichte ihn, zusätzliches Material einzuarbeiten, vor allem seine Beziehung zu Arved Fuchs, genauer zu beschreiben und zu artikulieren. Auch ermöglichte das spätere Redigieren, seine Recherchen über alte Antarktisreiseberichte und die antiken Schriften mit in seinen Bericht einzubauen. Messner war sich früh darüber im Klaren, dass so eine Expedition ohne umfangreiche Vorbereitungen und finanzielle Unterstützung nicht möglich gewesen wäre. Dies gilt besonders heute, ohne umfangreiches Sponsoring ist ein solches Projekt nicht realisierbar. Heute gilt allerdings mehr die Tatsache, dass eine solche Expedition vor allem spektakulär sein muss: je extremer und spektakulärer, desto wahrscheinlicher ist es, dass man auch gesponsert wird . Messner hat den modernen Reisebericht an sich modernisiert, spektakulärer und vor allem öffentlicher gemacht. Der Forscherdrang wird allerdings auch ersetzt durch den persönlichen Wunsch des Individuums, sich selbst zu verwirklichen. Messner hat mit seinem Reisebericht beides geschafft: er hat zum einen sich selbst verwirklicht und zu anderen hat er auf die Unberührtheit und die Schönheit der Antarktis aufmerksam gemacht. Ob es einer anderen Person gelungen wäre, eine ähnlich breite Masse mit seinem Antarktisreisebericht zu erreichen, sei dahingestellt. Wahrscheinlicher ist jedoch, dass Messner als „öffentliche Person“ eben diese Fähigkeit hatte, für die Antarktis zu begeistern. Dies hat er bei mir definitiv geschafft und ich sehe heute die Antarktis unter einem ganz anderen Aspekt, als es vor dem Lesen seines Buches Antarktis als Reisebricht der Fall war. Unlike earlier expeditions which were driven by the mere attraction of the unexplored continent Antarctica, leading to physical and mental efforts as a global “exploration mission” for the information seeking world, today’s explorers are less focused on a scientific aspect rather than the “extreme experience” of Antarctica. A contemporary adventurer is on a constant quest for the ultimate “kick” – the message is: more extreme equals better. He wants to explore his own limits and exposes himself to all possible trials, to fulfil his own character in order to know how much he can expect of himself and this “superhuman” task. Antarctica is the perfect location to meet this extreme experience, also regarding the way to communicate one’s experience to the public. Regarding a possible traveller’s library (if the modern adventurer decides to take one with him), he would choose a digitalized one: during the planning process he can easily download all books of interest on his Kindle or his Tablet-PC, having all publications of previous Antarctica explorers at his disposal very quickly. As a matter of fact, a modern explorer is not exploring alone anymore. During his entire exploration he can get connected through all possible modern social media channels (Facebook, Twitter, Blog etc.) and share his own experience with a broad online public. As a result, he will constantly be accompanied by media and users. Unlike former Antarctica explorers, or even Reinhold Messner himself, a contemporary explorer will be a networked one. It won’t take months until the explorer has published all his impressions, his experience or his research results – he can do it immediately, in real time and (in a certain way) even unfiltered. The problems, however, are obvious: a direct and unfiltered communication prevents an editing process in a later stage of the travelling report’s publication, so that even unintended or unpleasant facts can be published unintentionally. Messner’s travel report can be regarded as one of the last “classic” travel reports for Antarctica: planning, the exploration itself and writing were conducted under “old school” circumstances. Messner has published his report only months after his exploration, which allowed him to add additional information and to describe these details in detail, above all his relationship to Arved Fuchs. Later editing tasks made it possible to incorporate quotes from ancient sources and own research results of previous Antarctica explorations. Messner was aware on a very early stage that his expedition would not have been possible without thorough preparations and financial support. This rule specifically applies to our modern times; such a project is not feasible without extensive sponsoring. Above all, a modern expedition has to be spectacular: the more extreme and spectacular, the more likely it is to gain sponsors . Messner has modernized contemporary travel reports by making it more spectacular and public. The explorer’s spirit was, however, replaced by the individual drive to prove and satisfy his own personal ego. Messner was successful in both aspects: he has proven himself on one hand, and caused an increased attention to the untouched beauty of Antarctica on the other hand. Nevertheless, it is questionable if any other person than Messner could have reached such a broad public audience. It is, however, more likely that Messner as a “public person” had this ability to elate the public for Antarctica. He definitely did it in my case, and now I see Antarctica under completely different pretences than I did before reading his book “Antarktis als Reisebericht”. Abstract Unlike earlier expeditions which were driven by the mere attraction of the unexplored continent Antarctica, leading to physical and mental efforts as a global “exploration mission” for the information seeking world, today’s explorers are less focused on a scientific aspect rather than the “extreme experience” of Antarctica. A contemporary adventurer is on a constant quest for the ultimate “kick” – the message is: more extreme equals better. He wants to explore his own limits and exposes himself to all possible trials, to fulfil his own character in order to know how much he can expect of himself and this “superhuman” task. Antarctica is the perfect location to meet this extreme experience, also regarding the way to communicate one’s experience to the public. Regarding a possible traveller’s library (if the modern adventurer decides to take one with him), he would choose a digitalized one: during the planning process he can easily download all books of interest on his Kindle or his Tablet-PC, having all publications of previous Antarctica explorers at his disposal very quickly. As a matter of fact, a modern explorer is not exploring alone anymore. During his entire exploration he can get connected through all possible modern social media channels (Facebook, Twitter, Blog etc.) and share his own experience with a broad online public. As a result, he will constantly be accompanied by media and users. Unlike former Antarctica explorers, or even Reinhold Messner himself, a contemporary explorer will be a networked one. It won’t take months until the explorer has published all his impressions, his experience or his research results – he can do it immediately, in real time and (in a certain way) even unfiltered. The problems, however, are obvious: a direct and unfiltered communication prevents an editing process in a later stage of the travelling report’s publication, so that even unintended or unpleasant facts can be published unintentionally. Messner’s travel report can be regarded as one of the last “classic” travel reports for Antarctica: planning, the exploration itself and writing were conducted under “old school” circumstances. Messner has published his report only months after his exploration, which allowed him to add additional information and to describe these details in detail, above all his relationship to Arved Fuchs. Later editing tasks made it possible to incorporate quotes from ancient sources and own research results of previous Antarctica explorations. Messner was aware on a very early stage that his expedition would not have been possible without thorough preparations and financial support. This rule specifically applies to our modern times; such a project is not feasible without extensive sponsoring. Above all, a modern expedition has to be spectacular: the more extreme and spectacular, the more likely it is to gain sponsors . Messner has modernized contemporary travel reports by making it more spectacular and public. The explorer’s spirit was, however, replaced by the individual drive to prove and satisfy his own personal ego. Messner was successful in both aspects: he has proven himself on one hand, and caused an increased attention to the untouched beauty of Antarctica on the other hand. Nevertheless, it is questionable if any other person than Messner could have reached such a broad public audience. It is, however, more likely that Messner as a “public person” had this ability to elate the public for Antarctica. He definitely did it in my case, and now I see Antarctica under completely different pretences than I did before reading his book “Antarktis als Reisebericht”.